SiDal Development (Laboratory Big Data System) in Basic Physics Laboratory - Hana Susanti; Cahyo Puji Asmoro; Hendri Sulistyo (Universitas Khairun, 2023)
Inventory activities for tools and materials, borrowing tools, free laboratory processes and much more, are part of the Education laboratory services, in its function as a support for the Tri Dharma of Higher Education. These activities when carried out with conventional systems, require a long time with less-than-optimal results. To improve laboratory management services, a device data collection system was developed which is contained in a web-based application, called SiDal (Laboratory Big Data System). SiDal is a subsystem of the laboratory management system at the Basic Physics Laboratory of FPMIPA UPI. The aim of developing SiDal is for laboratory services to be more effective and efficient with optimal results. Users can access tool data, tool catalog, tool status and where to store the tool. To see the success of the system, research was carried out using the Research and Development method. Trials of the application of this system were carried out at the Basic Physics Laboratory of FPMIPA UPI by conducting surveys through questionnaires and interviews. From the results of the questionnaire distributed, 68 student respondents from various generations had accessed SiDal. 98% of respondents agreed that the implementation of SiDal in the Basic Physics Laboratory provided an increase in laboratory management services. The results obtained will serve as an evaluation and further development of the laboratory management system.